Sweetpotato cultivars responses to interactive effects of warming, drought, and elevated carbon dioxide - Taduri, Shasthree; Bheemanahalli, Raju; Wijewardana, Chathurika; Lone, Ajaz A.; Meyers, Stephen L.; Shankle, Mark; Gao, Wei; Reddy, K. Raja (Frontiers in Genetics, 2023)
Plants are sensitive to changes projected in climates, such as elevated carbon dioxide (eCO2), high temperature (T), and drought stress (DS), which affect crop growth, development, and yield. These stresses, either alone or in combination, affect all aspects of sweetpotato plant growth and development, including storage root development and yield. We tested three sweetpotato cultivars (Beauregard, Hatteras, and LA1188) responses to eight treatments (Control, DS, T, eCO2, DS+T, T+eCO2, DS+eCO2, DS+T+eCO2). All treatments were imposed 36 days after transplanting (DAP) and continued for 47 days. Treatments substantially affected gas exchange, photosynthetic pigments, growth, and storage root components. Cultivars differed considerably for many of the measured parameters. The most significant negative impact of DS was recorded for the shoot and root weights. The combination of DS+T had a significant negative effect on storage root parameters. eCO2 alleviated some of the damaging effects of DS and high T in sweetpotato. For instance, eCO2 alone or combined with DS increased the storage root weights by 22 % or 42 % across all three cultivars 42 %, respectively. Based on the stress response index, cultivar ‘Hatteras’ was most tolerant of individual and interactive stress, and ‘LA 1188’ was sensitive. Our findings suggest that eCO2 negates the negative of T or DS on the growth and yield of sweetpotato. We identified a set of individual and interactive stress-tolerant traits that can help select stress cultivars or breed new lines for future environments.